Assessment of Anatomical Variations in the Anterior Loop of the Mental Nerve in the Northeast Population to Estimate a Safe Zone for Implant Prosthesis: An Institution-Based Study - Hamari Debbarma; Jogeswar Barman; Sonu Agarwala; Barasha Goswami; Alak Bhattacharyya; Joshni Loitongbam (Wolters Kluwer Medknow Publications, 2024)
Background: The precise location of the anterior loop is of utmost importance during implant surgery to avoid any postoperative complications. The aim of the institution-based study was to determine the prevalence of the anterior loop with respect to age and gender in the northeast population. Materials and Methods: Sixty outpatients opting for implant prostheses in the interforaminal region of the mandible were enrolled in this study based on the inclusion and exclusion criteria. Results: The anterior loop was identified in 18.3% of the total subjects, and the mean length of the anterior loop was found to be 3.37 ± 0.53 mm. Planning for prosthetic-driven the implant placement was possible in 54.5% of the subjects. Conclusions: Proper treatment planning using cone beam computed tomography (CBCT) with a radiographic stent is paramount important for the safe placement of implant in the presence of the anterior loop of the mental nerve.